A new species of Utricularia L. (Lentibulariaceae) from the Chapada Diamantina, Bahia, Brazil - Campos, Gleidineia Leite; Cheek, Martin; Giulietti, Ana Maria (SITIENTIBUS série Ciências Biológicas, 2010)
A new species of the genus Utricularia is described from the Chapada Diamantina, in the state of Bahia. Utricularia catolesensis G. L. Campos, M. Cheek & Giul. is morphologically related to Utricularia purpureocaerulea A. St. Hil. & Girard, differing from it by its acute to subacute sepals, the white or rarely lilac corolla, basal hump on lower lip yellowish white and seeds pyramidal. The species occurs in swamps, in grassy areas or at the margins of streams.